Bioremediasi Tanah Tercemar Timbal pada Tempat Pemrosesan Akhir Sampah Jalupang Kabupaten Karawang menggunakan Teknologi Vermicomposting - Ardiansyah, Alvi Husni; Sari, Gina Lova; Ratnawati, Kania (Universitas Tanjungpura, 2025)
The Final Waste Processing Site (TPA) Jalupang is a landfill located in Karawang Regency that has been operating since 2003, with a total area of 6.9 hectares and an effective area of 4.7 hectares. For 22 years, TPA Jalupang has operated using the open dumping method, which poses a risk of heavy metal contamination, including lead (Pb). One method for removing heavy metals from soil is through vermicomposting technology. Therefore, this study aims to evaluate the effectiveness of vermicomposting in reducing lead (Pb) concentrations in contaminated soil. This research was conducted experimentally on a laboratory scale over 56 days using reactors with a capacity of 55 liters. The experimental variations involved different ratios of contaminated soil and vermicompost feedstock: 0:2 and 2:0 (as controls), as well as 1:2 and 2:1 (w/w), with the addition of 75 earthworms under aerobic conditions. Throughout the experiment, pH, temperature, and moisture content were monitored, along with periodic measurements of the C/N ratio and lead concentration every 14 days. During the vermicomposting process, environmental conditions with temperatures ranging from 29.0